2017
DOI: 10.13075/mp.5893.00584
|View full text |Cite
|
Sign up to set email alerts
|

Can diabetes be treated as an indirectly work-related disease?

Abstract: In this article the authors attempted to analyze the arguments for considering diabetes as a work-related disease. An overview of literature has been done out of articles published in the years 1980-2016, with the use of combination of key words referring to employment, workplace, and diabetes. The PubMed database was the source of data. The authors indicate that the following arguments are in favor of diabetes being recognized as a work-related disease: diabetes is not an occupational disease, it is not direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The analyses indicated that the risk of a lack of knowledge about how to prevent diabetes was higher in men, as well as in people with a low level of education, not married, without obesity, non-diabetic and without diag-betes do not admit their illness, do not use their benefits in the workplace (shorter daily working hours and longer holidays), and accept working conditions that can negatively affect the process of the disease [23]. Meanwhile, both international and Polish recommendations suggest that diabetes cannot be the cause of discrimination or unequal treatment in the workplace, and that occupational restrictions should be considered on a case-by-case basis [24]. Occupational activity of people suffering from diabetes not only guarantees them and their families financial stability, but also affects their mental health, gives a sense of value and independence, as well as helps to maintain social relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analyses indicated that the risk of a lack of knowledge about how to prevent diabetes was higher in men, as well as in people with a low level of education, not married, without obesity, non-diabetic and without diag-betes do not admit their illness, do not use their benefits in the workplace (shorter daily working hours and longer holidays), and accept working conditions that can negatively affect the process of the disease [23]. Meanwhile, both international and Polish recommendations suggest that diabetes cannot be the cause of discrimination or unequal treatment in the workplace, and that occupational restrictions should be considered on a case-by-case basis [24]. Occupational activity of people suffering from diabetes not only guarantees them and their families financial stability, but also affects their mental health, gives a sense of value and independence, as well as helps to maintain social relationships.…”
Section: Discussionmentioning
confidence: 99%
“…People working at night, often taking overtime, having sedentary work or exposed to permanent stress in the workplace are at a higher risk of developing diabetes. It, therefore, underlines the need for diabetes screening among people at risk of occupational nuisance, as well as the need for education aimed at modifying the lifestyles of office workers, including greater physical activity and weight reduction, reduction of stressors, improved psychosocial conditions, as well as access to healthy food and opportunities for walking breaks in the workplace [24]. Given the social, economic and health-related costs of diabetes, the low level of knowledge about how to prevent diabetes and its consequences in the Polish society may be a concern.…”
Section: Discussionmentioning
confidence: 99%